2020
DOI: 10.1021/acs.est.9b06034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Environmental Persistence and Inactivation of MS2 Bacteriophage and the Presumed Ebola Virus Surrogate Phi6 Using Low Concentration Hydrogen Peroxide Vapor

Abstract: Ebola virus (EBOV) disease outbreaks, as well as the ability of EBOV to persist in the environment under certain conditions, highlight the need to develop effective decontamination techniques against the virus. We evaluated the efficacy of hydrogen peroxide vapor (HPV) to inactivate MS2 and Phi6 bacteriophages, the latter a recommended surrogate for EBOV. The phages were inoculated onto six material types with and without the presence of whole human blood. The inoculated materials were then exposed to either a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 39 publications
2
51
0
Order By: Relevance
“…For example, the disinfectant spray (H 2 O 2 /NaOCl) is commonly suggested to inactivate the enveloped virus from the waste surface ( Gallandat et al, 2017 ), but this cannot work in each of the cases. The presence of blood on fomites would require a much higher dosage of disinfectant ( Wood et al, 2020 ) that can be better understood for several other circumstances by interdisciplinary researches.…”
Section: Recommendationsmentioning
confidence: 99%
“…For example, the disinfectant spray (H 2 O 2 /NaOCl) is commonly suggested to inactivate the enveloped virus from the waste surface ( Gallandat et al, 2017 ), but this cannot work in each of the cases. The presence of blood on fomites would require a much higher dosage of disinfectant ( Wood et al, 2020 ) that can be better understood for several other circumstances by interdisciplinary researches.…”
Section: Recommendationsmentioning
confidence: 99%
“…The transmission pathway of infected blood, and the protective nature of the blood matrix as shown by Fischer et al (22), led to the use, in the current study, of ATS as a blood stimulant, as it contains proteins, hemoglobin, and carbohydrates. Though testing only continued for 72 h, Wood et al demonstrated better persistence of phi 6 when suspended in blood diluent than in phosphate-buffered saline (PBS) ( Table 1) and that the influence of the matrix overshadowed the influence of the fomite material (43). The current data show that phi 6 infectivity persists longer in dried ATS (18°C, 20% RH, 3.04 g/m 3 AH) than the Ebola Makona-WPGC07 strain persisted in blood under similar, but not exact, conditions (21°C, 40% RH, 7.35 g/m 3 AH) (22).…”
Section: (21 55-70) N/a N/a N/a 1 H (3) 34 Sars-cov-1 Cotton Gown Grmentioning
confidence: 99%
“…30,31 Bacteriophage MS2 is a non-enveloped virus that has been used as a surrogate in studies looking at airborne RNA viral pathogens, as well as disinfectant studies performed by the U.S. EPA. [32][33][34] G. stearothermophilus spores have been used in the study of PAA decontamination of surfaces. 35 Our findings are consistent with previous studies that demonstrated the efficacy of the PAA disinfection system.…”
Section: Discussionmentioning
confidence: 99%